Abelson murine leukemia virus: structural requirements for transforming gene function. - Srinivasan, A (1982)
The integrated Abelson murine leukemia virus (A-MuLV) genome cloned in bacteriophage lambda gtWES.lambda B was used to localize viral genetic sequences required for transformation. Comparison of the biological activity of cloned A-MuLV genomic and subgenomic fragments showed that subgenomic clones that lacked the 5' long terminal repeat and adjoining sequences (300 base pairs downstream of the repeat) were not biologically active. In contrast, subgenomic clones that lacked the 3' long terminal repeat and as much as 1.3 kilobase pairs of the A-MuLV cell-derived abl gene were as efficient as wild-type viral DNA in transformation. The A-MuLV-encoded polyprotein P120 and its associated protein kinase activity were detected in transformants obtained by transfection with Cla I, BamHI, and HindIII subgenomic clones. In contrast, individual transformants obtained with subgenomic Sal I clones expressed A-MuLV proteins ranging in size from 82,000 to 95,000 daltons. Each demonstrated an associated protein kinase activity. These results provide direct genetic evidence that only the proximal 40% of abl with its associated 5' helper viral sequences is required for fibroblast transformation.